Fostering Reading Habits: The Impact of the Reading Corner Program in Elementary Schools - Apriyani, Reni; Elizar (Universitas Pendidikan Ganesha, 2024)
Reading interest among students remains a significant challenge in education, particularly at the elementary level. This study aims to evaluate the role of university students participating in the Teaching Campus Program in fostering students' reading interest through the development of the Reading Corner initiative. A qualitative approach was employed, utilizing methods such as observation, in-depth interviews, focus group discussions, and document analysis to gather comprehensive data. The findings revealed that the Reading Corner Program had a substantial impact on increasing students' reading interest. Prior to the program's implementation, only 20% of students actively engaged in reading activities, but this figure surged to 98% after the program was introduced. The program's success was attributed to the provision of books aligned with students' interests, interactive reading activities, and the integration of literacy practices into the learning process. Despite challenges such as limited school facilities, the program successfully created an engaging learning environment that actively encouraged student participation. The study concludes that the Reading Corner Program effectively promotes a reading culture among students while maximizing the role of university students in literacy development. These findings underscore the importance of similar initiatives to strengthen student literacy as part of a sustainable strategy for improving educational quality.